2008
DOI: 10.1007/s12253-008-9115-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Soluble HER2 and Transforming Growth Factor Beta-1 Serum Levels in Gestational Trophoblastic Disease

Abstract: HER2/neu and TGF-beta1 are over-expressed in various types of malignancies. It appears that they play an important role in the biologic behavior of tumors and have prognostic value. Gestational tropoblastic diseases (GTDs) comprise of a heterogeneous group characterized by abnormally proliferating trophoblastic tissues, ranging from benign to malignant. The objective of this study was to measure and compare the serum levels of s-HER2 and TGF-beta between patients with GTDs and pregnant and non-pregnant control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Yang et al reported a prognostic value of 84% for percentage of cytorophoblasts with positive cytoplasmic immunostaining to predict the malignant progression of simple molar pregnancy ( 16 ). However, there are conflicting reports: Cameron et al reported the expression of c-erbB-2 in only one case out of 20 patients with persistent gestational trophoblastic disease ( 34 ); Dehaghani AS et al found that the mean serum c-erbB-2 does not differ significantly between GTD patients and normal pregnant controls ( 35 ). In contrast to these reports, we found an over expression of c-erbB-2 in cytotrophoblast of patients with GTN and complete mole with significant difference to simple molar pregnancy and partial mole.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al reported a prognostic value of 84% for percentage of cytorophoblasts with positive cytoplasmic immunostaining to predict the malignant progression of simple molar pregnancy ( 16 ). However, there are conflicting reports: Cameron et al reported the expression of c-erbB-2 in only one case out of 20 patients with persistent gestational trophoblastic disease ( 34 ); Dehaghani AS et al found that the mean serum c-erbB-2 does not differ significantly between GTD patients and normal pregnant controls ( 35 ). In contrast to these reports, we found an over expression of c-erbB-2 in cytotrophoblast of patients with GTN and complete mole with significant difference to simple molar pregnancy and partial mole.…”
Section: Discussionmentioning
confidence: 99%
“…Dave et al ( 21 ) found that higher TGF-β1 levels were exhibited in the serum of breast cancer patients. Furthermore, Dehaghani et al ( 22 ) revealed that the TGF-β1 serum levels were significantly higher in gestational trophoblastic disease patients when compared with those in pregnant and non-pregnant controls.…”
Section: Discussionmentioning
confidence: 99%